Pengaruh Electronic Word of Mouth dan Brand Image Terhadap Keputusan Pembelian Mixue di Cabang Jalan Braga - Rachel Dian Nitami Sinaga; Nur Hayati (CV. Ulil Albab Corp, 2024)
Brand image is the most important factor in consumers' decision to buy the product. A good impression of a brand can also increase sales by convincing consumers to try, through electronic word of mouth consumers can find out reviews of a brand. In this research, quantitative research is used because the research data used is in the form of numbers and analyzed using statistics. The sampling technique in this research is non-probability sampling using a purposive sampling method (purposeful sampling). The Adjusted R Square value or coefficient of determination obtained is 0.711. It can be concluded that the independent variables electronic word of mouth (X1) and Brand Image (X2) have an influence on purchasing decisions (Y) of 71.1%. Meanwhile, the remainder, namely 28.9%, was influenced by other variables not examined in this research.